[Letter re: proposed budget for ILMC 1999] - KAISER,H (Tufts Archival Research Center, 2007)
Missing Attachments; Letter to tobacco industry representatives from Harry Kaiser regarding the1999 proposed budget. Discusses pre-approved 10% budget increases for each of the next three years.